Antimicrobial and Attractant Roles for Chemerin in the Oral Cavity during Inflammatory Gum Disease - Godlewska, Urszula; Brzoza, Piotr; Sroka, Aneta; Majewski, Pawel; Jentsch, Holger; Eckert, Martin; Eick, Sigrun; Potempa, Jan; Zabel, Brian A.; Cichy, Joanna (Frontiers in Immunology, 2017)
Periodontal inflammation is one of the most common chronic inflammatory conditions in humans. Despite recent advances in identifying and characterizing oral microbiota dysbiosis in the pathogenesis of gum disease, just how host factors maintain a healthy homeostatic oral microbial community or prevent the development of a pathogenic oral microbiota remains poorly understood. An important determinant of microbiota fate is local antimicrobial proteins. Here, we report that chemoattractant protein chemerin, which we recently identified as a potent endogenous antimicrobial agent in body barriers such as the skin, is present in the oral cavity under homeostatic and inflammatory conditions. Chemerin and a chemerin-derived antimicrobial peptide are bactericidal against select bacteria strategically positioned in dental biofilm. Gingival crevicular samples from patients with gingivitis but not periodontitis contain abundant bioactive chemerin capable of inducing CMKLR1-dependent leukocyte migration. Gingipains secreted by the periodontopathogen P. gingivalis inactivate chemerin. Together, these data suggest that as an antimicrobial agent and leukocyte chemoattractant, chemerin likely contributes to antimicrobial immune defense in the oral cavity.